A interdisciplinaridade como proposta pedagógica para o ensino de estatística na educação básica - Pagan, Maria Adriana (2010)
The objective of this study was to compare the learning gains of three different student groups in first year high school who had contact with elementary concepts of statistics from Mathematics lessons (GM), Geography (GG) and Mathematics lessons applied interdisciplinary (statistics taught from Geography, Biology, Physics and Chemistry contents) (GI). To achieve this aim a study was done on a quasi-experimental basis which consisted of three groups of 35 students each at a public school in the state of São Paulo. It was applied two diagnostic tests (pre and post-test) at the study and the intervention was performed in each group by different teachers composing GM, GG and GI groups. The theoretical framework of this study included the theory of semiotics Records Offices of Raymond Duval (1995) about the change in registration; studies by Curcio (1989) and Wainer (1992) regarding to the levels of reading and interpreting data in graphs and tables respectively and the Literacy, Reasoning and Statistical Thinking with several authors as Cazorla (2002, 2005), Gal (2002), Lopes (2004), Morais (2006), Silva (2007) and Campos (2007). The interdisciplinary aspects were based on Fazenda (1994), Klein (2007) and Lenoir (2007) and the arithmetics in Novaes and Coutinho (2008). The study aimed to answer the following question: "What are the contributions that an educational intervention based on the principles of interdisciplinarity bring to the learning of statistics?" To answer this question the study was based on quantitative analysis of the results obtained in the tests applied to the three groups and a qualitative analysis of results presented by the students in the GI. The analysis showed a gain with the use of educational intervention at the three groups GM, GG and GI on the statistical study (construction, interpretation and arithmetic), but one significant performance was presented by students of the interdisciplinary group after educational intervention. This result allowed inferring that the teaching of Statistics based on an interdisciplinary approach proved its effectiveness as the interest of students in dealing with issues as well as their knowledge were reinforced by their understanding of statistical elements